Araticum reproductive phenology and its implications for productive potential - de Melo, Aniela Pilar Campos; Seleguini, Alexsander; Leite, Anderson Fernandes; de Souza, Eli Regina Barboza; Naves, Ronaldo Veloso (Comunicata Scientiae, 2015)
The araticum (Annona crassiflora Mart.) is a native fruit from the Cerrado biome, with a great economic and social potential. Studies on Cerrado native plants phenology are scarce and can be promising for a better rational and sustainable exploitation of its potentialities. Thus, the objective of this study was to characterize araticum reproductive phenology in the Cerrado. The phenophases evaluations were carried out from August 2008 to August 2010, in Goiania, Goias, Brazil, through counting of flower buds, flowers in anthesis and fruits formed. The production capacity was estimated through the effective fruiting rate. For flower emission, a biannual pattern was observed for araticum.. The effective fruiting rate observed was 3.29% and the araticum’s reproductive phenophases were concentrated during the rainy season. The effective fruiting rate is considered very low and depends on biotic and abiotic factors.